Knowledge management in science and technology enterprises in Vietnam - Tuyen, Hoang Van (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Science and Technology (S&T) enterprises and knowledge based enterprises in general are positioned in center of interest of researchers and policy makers for S&T development of Vietnam. This is seen clearly through numerous documents of the Party and the State of Vietnam1. However, the problem is how to mobilize the knowledge and the knowledge management in this type of enterprises. This paper is a contribution to clarify some aspects of knowledge and knowledge management in some typical S&T enterprises. Code: 13040101